Way to New Historical Memory? Creating a Vision of the Past in Pop Culture on the Example of World War II - Gralik, Dawid (Sensus Historiae, 2019)
The article raises the problem of the influence of pop culture, in the form of blogbusters and AAA video games, on historical memory related to World War II, especially in the Polish context. The article presents the image of World War II emerging from the opuses of pop culture, listed the opportunities and threats resulting from using films and video games as sources of knowledge, and analyzed their impact on the historical memory of Poles based on research conducted in this area.